Climate Risk Country Profile : Mongolia - World Bank Group; Asian Development Bank (World Bank, Washington, DC and Asian Development Bank, Manila, 2021)
Mongolia’s vast steppe plains and deserts experience about 250 sunny days every year, leading to the country commonly being termed the land of the blue sky. Historical climate warming is believed to have taken place at some of the fastest rates in the world in Mongolia and other shifts in climate dynamics are already strongly impacting on lives and livelihoods. This document aims to succinctly summarize the climate risks faced by Mongolia. This includes rapid onset and long-term changes in key climate parameters, as well as impacts of these changes on communities, livelihoods, and economies, many of which are already underway. This is a high-level synthesis of existing research and analyses, focusing on the geographic domain of Mongolia, therefore potentially excluding some international influences and localized impacts. The core data presented is sourced from the database sitting behind the World Bank Group’s (WBG) climate change knowledge portal (CCKP), incorporating climate projections from the Coupled Model Inter-comparison Project Phase 5 (CMIP5). This document is primarily meant for WBG and Asian Development Bank (ADB) staff to inform their climate actions and to direct them to many useful sources of secondary data and research.